2023
DOI: 10.3390/nu15102347
|View full text |Cite
|
Sign up to set email alerts
|

Metal Homeostasis and Exposure in Distinct Phenotypic Subtypes of Insulin Resistance among Children with Obesity

Abstract: Background: Trace elements and heavy metals have proven pivotal roles in childhood obesity and insulin resistance. However, growing evidence suggests that insulin resistance could encompass distinct phenotypic subtypes. Methods: Herein, we performed a comprehensive metallomics characterization of plasma samples from children and adolescents with obesity and concomitant insulin resistance, who were stratified as early (N = 17, 11.4 ± 2.4 years), middle (N = 16, 11.8 ± 1.9 years), and late (N = 33, 11.7 ± 2.0 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although it was initially designed for MS-based metabolomics, it should be noted that QC omics can also be used to manage other omics and MS data. In this sense, we would like to stress that some features of this QC protocol have successfully been applied in recent metabolomics and metallomics studies, which highlights its reliability to deal with complex and heterogeneous data. Therefore, we strongly believe that QC omics will facilitate the implementation of good QC practices, at both application and reporting levels, and thus become a gold standard in metabolomics research.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was initially designed for MS-based metabolomics, it should be noted that QC omics can also be used to manage other omics and MS data. In this sense, we would like to stress that some features of this QC protocol have successfully been applied in recent metabolomics and metallomics studies, which highlights its reliability to deal with complex and heterogeneous data. Therefore, we strongly believe that QC omics will facilitate the implementation of good QC practices, at both application and reporting levels, and thus become a gold standard in metabolomics research.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, parental obesity was associated with unhealthier outcomes in the offspring (e.g., IR, inflammation and unfavorable lipid profile), in close relationship with exacerbations in the aforementioned metal alterations (i.e., increased copper‐to‐zinc ratios and iron deficiency in circulation, and metal accumulation within erythrocytes). The stratification of the study population according to the insulin secretion profile in response to an oral glucose tolerance test enabled us to demonstrate that participants with late insulin peak, who are characterized by worsened IR and lipid profile, also showed sharpened disturbances in circulating levels of various metals and metalloids 49 . On the one hand, we found children with delayed hyperinsulinemia to have lower plasma contents of chromium and cobalt, which were in turn strongly correlated to various markers of hyperglycemia and dyslipidemia in a negative fashion, probably as a reflection of their vital role in controlling glucose and lipid metabolisms.…”
Section: Interindividual Variability Factors Influencing the Associat...mentioning
confidence: 99%
“… 5 7 . Previous studies have reported that exposure to As, Cd, cobalt (Co), Pb, and mercury (Hg) could cause chronic diseases such as diabetes and obesity 8 10 .…”
Section: Introductionmentioning
confidence: 99%